Enhanced Water Dispersibility of Curcumin Encapsulated in Alginate-Polysorbate 80 Nano Particles and Bioavailability in Healthy Human Volunteers - Govindaraju, Roopa; Karki, Roopa; Chandrashekarappa, Jayanthi; Santhanam, Mukunthan; Shankar, Akshay K.K.; Joshi, Hanumanthachar K.; Divakar, Goli (Pharmaceutical Nanotechnology, 2019)
Background: The turmeric (Curcuma longa) plant, a perennial herb of the ginger family, is an agronomic crop in the south and southeast tropical Asia. Turmeric an Indian yellow gold and universal spice is described in Ayurveda, an ancient treatise on longevity and quality life for the treatment of various inflammatory disorders. The oral bioavailability of curcumin is low due to poor aqueous solubility, alkaline instability and speedy elimination. Objective: The present study is designed to prepare alginate polysorbate 80 nanoparticles to enhance aqueous solubility/dispersibility, hence bioavailability. Method: Curcumin-loaded alginate - polysorbate 80 nanoparticles were prepared by ionotropic gelation technique. Results: The optimized nano particles exhibited higher encapsulation efficiency (95%), particle size of 383 nm and Zeta potential of +200 mV. Formulations exhibited very low dissolution in Simulated Gastric Fluid (SGF) and Simulated Intestinal Fluid (SIF), but the major portion released in SCF which is attributed to the digestibility of alginate in Simulated Colonic Fluid (SCF) under the influence of colonic micro flora. FTIR and DSC observations revealed the successful entrapment of curcumin in alginate polysorbate-80 nanoparticles. The nanoparticles were more spherical, discrete and homogeneous. In healthy human volunteers, the oral bioavailability (AUC) of curcumin increased 5-fold after the consumption of curcumin nanosuspension compared to curcumin suspension. Maximum plasma concentration Cmax- 636 ± 122 ng/ml was observed at tmax- 2h for nanosuspension, whereas Cmax-87.7 ± 17.9ng/ml at tmax- 4h for suspension. Conclusion: Curcumin-loaded alginate - polysorbate 80 nanoparticles prepared by ionotropic gelation method, successfully entrapped curcumin. Both curcumin suspension and curcumin nanosuspension were safe and well tolerated and may thus be useful in the prevention or treatment of various inflammatory diseases of mankind.
Keywords: curcumin